Progress Report to the IMFC on the Activities of the Independent Evaluation Office of the IMF. (Policy Papers; Policy Paper ;, 2017)
Since the April 2017 report to the IMFC, the IEO has completed its evaluation on social protection, continued work on evaluations on fragile states and financial surveillance, initiated a new evaluation on advice on unconventional monetary policy, and advanced two updates.